Prevalence of Awareness in Total Intravenous Anesthesia: A Cross-Sectional Study: Awareness in Total Intravenous Anesthesia - Tariq, Maria; Zaman, Bakhtawar; Khan, Muhammad Arsalan; Rabbani, Sara; Khalid, .; Qureshi, Fayyaz Akhter (Pakistan Journal of Health Sciences, 2025)
reaction to stimuli, and the establishment of a tranquil surgical environment. Objective: To determine the prevalence of total intravenous anesthesia (TIVA) among patients in a tertiary care hospital. Methods: The research was a descriptive cross-sectional study. Total intravenous anesthesia was performed on 217 male and female patients aged 18–60 year. The patient’s history in the first two post-operative days revealed intraoperative consciousness. Data were gathered, from 17th June, to November 30th, 2022. Statistical analysis was performed using SPSS version 23.0. Results: The study found that the prevalence of awareness during total intravenous anesthesia (TIVA) was 15.7%, with a higher occurrence in patients with metabolic equivalent test scores ≤4 (45.4%, p < 0.001) and those with a previous history of awareness (80.0%, p < 0.001). Gender (16.4% in males vs. 14.1% in females, p = 0.654), age (15.2% in ≤45 vs. 16.0% in >45 years, p = 0.865), BMI (17.2% in ≤23.0 vs. 13.9% in >23.0 kg/m², p = 0.494), diabetes (13.3% in diabetics vs. 16.6% in non-diabetics, p = 0.558), alcoholism (25.0% in alcoholics vs. 15.1% in non-alcoholics, p = 0.360), and ejection fraction (20.0% in ≤40% vs. 14.7% in >40%, p = 0.403) did not show statistically significant associations with awareness prevalence. Conclusions: Metabolic equivalent scores and a prior history of awareness were significant predictors of intraoperative awareness during TIVA, highlighting the importance of tailored preoperative evaluations.